Sex, divoce and "machismo": about Gary Becker, Nobel Prize of Economy 1992 - Fernández-Baca, Jorge (1992)
Gary Becker has dedicated has devoted his life to extend the application of economic theory to all human activities. In his Treatise on the Family, Becker studies sexual discrimination, polygamy and monogamy, the choosing of mates, the demand for children and divorce, from the point of view of investing in human capital. It was perhaps this study that earned him the Nobel Prize for Economics. This article offers a view brief comment on this book.